IL-36γ Augments Host Defense and Immune Responses in Human Female Reproductive Tract Epithelial Cells - Winkle, Sean M.; Throop, Andrea L.; Herbst-Kralovetz, Melissa M. (Frontiers in Microbiology, 2016)
IL-36γ is a proinflamatory cytokine which belongs to the IL-1 family of cytokines. It is expressed in the skin and by epithelial cells (ECs) lining lung and gut tissue. We used human 3-D organotypic cells, that recapitulate either in vivo human vaginal or cervical tissue, to explore the possible role of IL-36γ in host defense against pathogens in the human female reproductive tract (FRT). EC were exposed to compounds derived from virus or bacterial sources and induction and regulation of IL-36γ and its receptor was determined. Polyinosinic-polycytidylic acid (poly I:C), flagellin, and synthetic lipoprotein (FSL-1) significantly induced expression of IL-36γ in a dose-dependent manner, and appeared to be TLR-dependent. Recombinant IL-36γ treatment resulted in self-amplification of IL-36γ and its receptor (IL-36R) via increased gene expression, and promoted other inflammatory signaling pathways. This is the first report to demonstrate that the IL-36 receptor and IL-36γ are present in the human FRT EC and that they are differentially induced by microbial products at this site. We conclude that IL-36γ is a driver for epithelial and immune activation following microbial insult and, as such, may play a critical role in host defense in the FRT.